Gagasan constitutional Complaint Sebagai kewenangan Baru Mahkamah Konstitusi dalam Perlindungan Hak Konstitusional - Herma Yanti (Universitas Batanghari Jambi, 2018)
The formation of the Constitutional Court (MK) as a guardian of the constitution is basically intended to guarantee the implementation of the constitutional provisions (the 1945 Constitution) seriously in the administration of the state, as well as to realize constitutional supremacy in the Indonesian legal state. One of the contents of the 1945 Constitution is a guarantee of protection of basic human and citizen rights that have been accepted as constitutional rights. Because of that, the Court also functions to guarantee the implementation of these constitutional rights. However, for violations of constitutional rights included in the case of constitutional complaints submitted to the Constitutional Court, the resolution has not yet been dealt with, because their authority has not been regulated in the 1945 Constitution, so the idea of making constitutional complaints develops as the Constitutional Court's new authority. This paper discusses how the Constitutional Court's authority in protecting constitutional rights is based on the 1945 Constitution, and what about the ideas that emerged to add constitutional complaint as the Constitutional Court's new authority in protecting constitutional rights. In accordance with the problem, this research is a normative legal research using a legal approach accompanied by a comparative legal approach. The results of the study show that the authority of the Constitutional Court in protecting constitutional rights is only limited to the authority to examine the Law against the Constitution. From the ideas that emerged, there were three possibilities for entering constitutional complaint on the authority of the Constitutional Court, namely through changes to the 1945 Constitution, through changes to the Law and through interpretation by the Constitutional Court itself. Of the three ideas, the most appropriate is to change the 1945 Constitution so that it can provide a strong foundation in providing protection for citizens' constitutional rights.